2018
DOI: 10.1159/000486397
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Burden of Stroke: The Dijon Stroke Registry (1987–2012)

Abstract: Background: We aimed to provide a representation of the global burden of stroke. Methods: All cases of stroke were prospectively identified through the population-based registry of Dijon, France (1987–2012). Attack rates and mortality rates (defined as stroke leading to death within 30 days) were standardized to the European standard. Sex differences and temporal trends were evaluated by calculating rate ratios (RRs). Results: In all, 5,285 stroke cases (52.7% women) were recorded. The standardized attack rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…This study was based on data from the Dijon Stroke Registry [4,5], an on-going population-based study that complies with the defined criteria for conducting "ideal" incidence stroke studies [6], and the guidelines for the reporting of incidence and prevalence studies in neuroepidemiology according to Standards of Reporting of Neurological Disorders [7]. Case-collection as well as adjudication procedures have been described extensively elsewhere [4,5].…”
Section: Study Population and Case-ascertainment Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on data from the Dijon Stroke Registry [4,5], an on-going population-based study that complies with the defined criteria for conducting "ideal" incidence stroke studies [6], and the guidelines for the reporting of incidence and prevalence studies in neuroepidemiology according to Standards of Reporting of Neurological Disorders [7]. Case-collection as well as adjudication procedures have been described extensively elsewhere [4,5].…”
Section: Study Population and Case-ascertainment Proceduresmentioning
confidence: 99%
“…Case-collection as well as adjudication procedures have been described extensively elsewhere [4,5]. To ensure the exhaustiveness of case-collection, multiple overlapping sources of information are used.…”
Section: Study Population and Case-ascertainment Proceduresmentioning
confidence: 99%
“…While some authors reported declining mortality following ICH in recent years [3,6,10], others found a decrease only in younger patients (<75 years of age) [12] or observed decreasing 30-day mortality but no changes within the first 48 hours from stroke onset [2]. Numerous studies, including a large meta-analysis by van Asch in 2010 that reached back into the 1980s, observed no change in mortality after ICH [1,79,11,13]. The aim of this analysis was to examine trends in ICH incidence, severity, complications, therapy and outcome of ICH from 2008 to 2016 in subjects registered in the Austrian Stroke Unit Registry (ASUR) [1416].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a global health problem, consisting the major reason of disability and death all over the world. It is well known that the older age, sex, and genetics are risk factors of stroke [ 1 ] however; according to Global Burden of Disease (GDB) 2013 STUDY, the burden of global stroke continues to increase globally. [ 2 ] Consequently, it is essential to find out other important genetic factors related to the mechanisms of the disease.…”
Section: Introductionmentioning
confidence: 99%